Контроль качества в фарфоро-фаянсовом производстве - Колотий П. В. Павел Васильевич; Шилов Ю. Ф. Юрий Федорович; Долин А. И. Авраам Иосифович; Комская М. С. Мариам Самсоновна (Киев, Технiка, 1983)
Авт. указаны на обороте тит. л.